Effect of bypass fat supplementation on production performance of lactating Mehsana buffaloes - SADRASANIYA, D A; PATEL, V K; PATIL, S S; PAWAR, M M; ANKUYA, K J (The Indian Journal of Animal Sciences, 2022)
An on-farm trial was conducted to study the effect of bypass fat supplementation in lactating Mehsana buffaloes for the period of 90 days post-calving in Banaskantha district, Gujarat. Fourteen Mehsana buffaloes were selected and randomly divided into two groups having 7 animalseach. The animals in the control (CON) group were fed on basal diet (concentrate mixture, green and dry fodder) and the treatment (BPF) group was fed basal diet supplemented with bypass fat @ 100 g/day/animal. Supplementation of bypass fat did not influence the DM intake and body weights. Higher milk yield (9.02%) and 6% fat corrected milk yield (14.23%) were observed in the BPF than the CON group. The percentages of milk fat (6.43 vs. 6.01%) and SNF (9.51 vs. 9.31%) were significantly higher in the BPF than the CON group. The feed conversion efficiency was significantly lower (0.99 vs. 1.07) in bypass fat fed group. Based on the findings, it was concluded that supplementation of bypass fat at the rate of 100 g/d in early lactating Mehsana buffaloes improved the milk yield, FCM yield, milk fat content, SNF and feed conversion efficiency.